"We can move forward": challenging historical inequity in public health research in Solomon Islands - Speare Richard; Muse Alwin; Harrington Humpress; Fa'anuabae Chillion E; Asugeni Rowena; MacLaren David J; Redman-MacLaren Michelle L; Clough Alan R (BMC, 2010)
Abstract Background In resource-poor countries, such as Solomon Islands, the research agenda on health is often dominated by researchers from resource-rich countries. New strategies are needed to empower local researchers to set directions for health research. This paper presents a process which seeks to enable a local and potentially more equitable research agenda at a remote hospital in Solomon Islands. Methods In preparation for a health research capacity-building workshop at Atoifi Adventist Hospital, Malaita, Solomon Islands, a computer-based search was conducted of Solomon Islands public health literature. Using a levels-of-agreement approach publications were categorised as: a) original research, b) reviews, c) program descriptions and d) commentaries or discussion. Original research publications were further sub-categorised as: i) measurement, ii) descriptive research and iii) intervention studies. Results were reviewed with Solomon Islander health professionals in a focus group discussion during the health research workshop. Focus group participants were invited to discuss reactions to literature search results and how results might assist current or future local researchers to identify gaps in the published research literature and possible research opportunities at the hospital and surrounding communities. Focus group data were analysed using a grounded theory approach. Results Of the 218 publications meeting inclusion criteria, 144 (66%) were categorised as 'original research', 42 (19%) as 'commentaries/discussion', 28 (13%) as 'descriptions of programs' and 4 (2%) as 'reviews'. Agreement between three authors' (MRM, DM, AC) independent categorisation was 'excellent' (0.8 <κ). The 144 'original research' publications included 115 (80%) 'descriptive studies' (κ = 0.82); 19 (13%) 'intervention studies' (κ = 0.77); and 10 (7%) 'measurement studies'(κ = 0.80). Key themes identified in the focus group discussion challenged historical inequities evident from the literature review. These included: i) who has done/is doing research in Solomon Islands (largely non-Solomon Islanders); ii) when the research was done (research needs to keep up to date); iii) amount of published research (there should be more); iv) types of research (lack of intervention and operational research); v) value of published research (important); vi) gaps in published literature (need more research about nursing); vii) opportunities for research action (start small); viii) support required to undertake research at the hospital and in surrounding communities (mentoring and partnering with experienced researchers). Conclusions A search and collaborative review of public health literature for Solomon Islands at a health research capacity building workshop has uncovered and challenged historical inequity in the conduct and access to public health research. Emerging Solomon Islander researchers at a remote hospital are now working to set priorities and strengthen local research efforts. These efforts have highlighted the importance of collaboration and mentoring for Solomon Islanders to instigate and implement public health research to improve the health of individuals and communities served by this remote hospital.